GAMBARAN KLINIS DAN RADIOLOGIS AFASIA PADA PASIEN STROKE ISKEMIK YANG TERDIAGNOSIS DI RS PON DALAM PANDEMI COVID - 19 TAHUN 2021 - Rasya Hapsari Danardhono, (2022)
Global aphasia, sensory transcortical aphasia, motor transcortical aphasia, motor aphasia, sensory aphasia, conduction aphasia and anomic aphasia can occur in ischemic stroke. There are different locations of lesions in each type of aphasia. Before the pandemic, global aphasia was the most common type of aphasia. This study was conducted to determine the type of aphasia, clinical and radiological features, and also management of aphasia in ischemic stroke during the pandemic. Methods: This research is a descriptive study with a cross sectional approach. Sampling was done by total sampling technique. The research sample was ischemic stroke patients with aphasia diagnosed from January 1, 2021 - December 31, 2021 at the National Brain Center Hospital Prof. Dr. dr. Mahar Mardjono Jakarta who met the restriction criteria. Results: There were 162 aphasic patients with ischemic stroke. Median age was 59.82 (range 34 - 87 years). Most patients were male (59.9%), aged 55-65 years (37.0%). Hypertension (90.1%), diabetes mellitus (50.0%), and dyslipidemia ( 75.9%) were the dominant risk factors. The most common type of aphasia is global aphasia (43.8%). The frontal lobe was the dominant location of global aphasia (38 patients). Whereas the temporal lobe was the dominant location of sensory aphasia (8 patients). In addition, basal ganglia was the dominant location of motor aphasia (28 patients). Furthermore, corona radiata was the dominant location in transcortical motor aphasia (4 people). However, sensory transcortical aphasia and anomic aphasia have no predominant lesion site. The therapy given to aphasic patients with a history of ischemic stroke includes speech therapy (85.2%), antiplatelet therapy (98.1%), anticoagulants (19.1%), rTPA (1.2%), and neuroprotectors (3.0 %). Conclusion: In ischemic stroke patients with aphasia at the National Brain Center Hospital during the pandemic (2021), global aphasia was found to be the most common (43.8%) with the dominant global aphasia lesion location in the frontal lobe (38 patients). This is in accordance with previous research which stated that global aphasia was the most common aphasia in ischemic stroke before the pandemic.